2009
DOI: 10.1111/j.1540-8159.2008.02198.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial of Defibrillation Thresholds from the Right Ventricular Outflow Tract and the Right Ventricular Apex

Abstract: DFTs in leads placed in the RVOT and RVA are comparable. RVOT ICD lead placement is safe and exhibits similar lead stability, threshold, and impedance measurements as the traditional RVA location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 7 publications
(15 reference statements)
2
18
0
4
Order By: Relevance
“…Our results are similar to previous studies [11][12][13][14]. Giudici et al (14) described their experience with a smaller cohort of 112 patients with RVNA defibrillator lead with an average follow up of 22.5 months [14].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are similar to previous studies [11][12][13][14]. Giudici et al (14) described their experience with a smaller cohort of 112 patients with RVNA defibrillator lead with an average follow up of 22.5 months [14].…”
Section: Discussionsupporting
confidence: 93%
“…Over time many patients with ICDs may require pacing due to a combination of disease progression, the effect of adjunctive drug therapy and the development of sinus and atrioventricular node disease. Previous studies have demonstrated that ICD leads placed in the RVNA have similar defibrillation thresholds [11][12][13] and long-term stability and performance as leads placed in the RV apex [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…Concerning defibrillation catheters, given their greater rigidity, it was supposed that the risk of perforation would be less elevated if infundibular septal pacing was conducted without affecting the pacing and defibrillation thresholds, as already discussed [28,[48][49][50]. The only randomized study designed to evaluate the feasibility and performance of RV mid-septal versus apical implantable defibrillator lead placement was recently published by Mabo et al [50].…”
Section: Septal Pacing and Defibrillation Leadsmentioning
confidence: 99%
“…[25][26][27] Furthermore, the place of MES was most commonly found in the septal locations, a site not commonly used in CRT-D. Septal placement of the implantable cardioverter defibrillator lead has good evidence for safety. 24 In our series, there were no implantable cardioverter defibrillator lead dislodgments, and the defibrillator test was successfully performed.In pacemakers, septal pacing has shown benefits over apical pacing in terms of LV function and synchrony. 19,20 Long-term apical pacing has been associated with interventricular dyssynchrony and HF.…”
mentioning
confidence: 99%
“…[25][26][27] Furthermore, the place of MES was most commonly found in the septal locations, a site not commonly used in CRT-D. Septal placement of the implantable cardioverter defibrillator lead has good evidence for safety. 24 In our series, there were no implantable cardioverter defibrillator lead dislodgments, and the defibrillator test was successfully performed.…”
mentioning
confidence: 99%